Estimating the Distributional Burden of General Sales Tax in Pakistan (The Pakistan Development Review, 2025)
Pakistan’s tax regime heavily relies on indirect taxes, constituting 60 percent of total tax receipts, of which general sales tax (GST) is a major component. This paper assessed who bears how much burden of GST levied on domestic production and sales by examining its incidence and distributional burden across household deciles for the year 2018-19. The paper maintained that even if the final product is exempted from tax, it incorporates the impact of taxes levied on intermediate inputs it uses. In order to trace these cascading effects of taxes, the paper used an input-output model-based approach. The results showed that the overall incidence of GST was, on average, 6.7 percent. The distribution of incidence was found to be regressive across the board as well as in rural and urban areas. Analysis by commodity groups indicated that basic food items bore the highest incidence and displayed the highest extent of regressivity across all deciles. This suggests that the poorer segments of society bear a relatively greater burden of GST in Pakistan.